2020
DOI: 10.1097/gox.0000000000003155
|View full text |Cite
|
Sign up to set email alerts
|

The Perception of the Ideal Body Contouring in Mexico

Abstract: Background: Over the centuries, our appreciation of beauty has changed, as has the social environment that influences our perspective. Currently we are trying to use measurable instruments to achieve a better aesthetic result in each patient, using as a reference the “golden ratio,” which is found in harmonies of all kinds—in art, nature, architecture, and today, in medicine—to aspire to the ideal proportion. Methods: We conducted a survey in which we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“… 65 Pérez et al showed survey participants four photoshopped versions of the same model, one with the golden ratio (1.61) and three with other proportions. 66 The picture in which WHR equaled the golden ratio was commonly voted as “the most attractive.” Another demographic analysis of ideal buttocks metrics to help surgery planning revealed the WHR of the most desirable buttocks from the posterior aspect to be 0.65, with 0.60 being the second most attractive ratio. 62
Figure 5 Posterior view with varying WHRs in women.
…”
Section: Discussionmentioning
confidence: 99%
“… 65 Pérez et al showed survey participants four photoshopped versions of the same model, one with the golden ratio (1.61) and three with other proportions. 66 The picture in which WHR equaled the golden ratio was commonly voted as “the most attractive.” Another demographic analysis of ideal buttocks metrics to help surgery planning revealed the WHR of the most desirable buttocks from the posterior aspect to be 0.65, with 0.60 being the second most attractive ratio. 62
Figure 5 Posterior view with varying WHRs in women.
…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, the high figures of dissatisfaction with BI found in the sample participants are striking. Only a small proportion wished to larger (people who perceived themselves to be too thin) and a larger percentage of people wished to be thinner, which was probably due to dissatisfaction with the excess of “redundant” skin, and lack of BI reorganization and redefinition demanded by their new physical appearance 50 and the desire for a muscular slim silhouette among men and defined slim silhouette with salient breasts and buttocks among Mexican women 51 .…”
Section: Discussionmentioning
confidence: 99%
“…4 A WHR of 0.65 to 0.70 is consistently considered highly attractive in the modern era. [5][6][7][8] The term "ant waist" is becoming popular for waists that are tiny and attractive. However, it is difficult for some people, such as transgender individuals, to achieve the ideal WHR even after abdominoplasty and buttock lift because of their bony structures.…”
Section: Introductionmentioning
confidence: 99%